Predictive factors of volumetric reduction in lumbar disc herniation treated by O2-O3 chemiodiscolysis - Negro, Alberto; Paolucci, Aldo; Russo, Camilla; Di Stasi, Martina; Guerriero, Pasquale; Arrigoni, Francesco; Bruno, Federico; Pagnini, Francesco; Angileri, Salvatore Alessio; Palumbo, Pierpaolo; Masciocchi, Carlo; Puoti, Gianfranco; et al. (Acta Biomedica Atenei Parmensis, 2020)
Purpose: Aim of this study is to assess the effectiveness of O2-O3 percutaneous chemiodiscolysis by evaluating volumetric changes in lumbar disc herniation on magnetic resonance imaging, in order to identify possible pre-treatment factors affecting such changes Methods: Between January 2014 and December 2017, a total of 87 patients with low back pain and 103 lumbar disc herniations with MRI confirmation were considered for O2-O3 chemiodiscolysis. The volume of each herniated disc was determined before and after the treatment. Results:  Multiple linear regression analysis showed a strong correlation between post-treatment LDH volume percent change and both pre-treatment LDH volume and pre-treatment EQ-VAS (p